Identification of indicators for sustainable urban water development planning - Maurya S.P.; Singh P.K.; Ohri A.; Singh R. (My University, 2025)
Rapid urbanization has put tremendous pressure on the extraction of natural water resources. Uncontrolled extraction of water has further created water stress in the urban sector. Therefore, it is the need of the day to have a positive water balance for sustainable development of an urban area. The sustainability of water cannot be simply seen as quantitative adequacy but it has other environmental dimensions such as depleting of the groundwater table, drainage problem, and pollution of surface water bodies etc. The present paper focuses on the development of a single index based on a combination of Integrated Urban Water Management (IUWM) and pressure-state-response (PSR) frameworks. In the proposed framework twenty-two sub-indicators have been brought down into seven broad categories to measure the relevant indicators. This single index termed as Water for Development Planning Index (WDPI) may be used for further development planning which will incorporate all aspects of urban water systems. Formulation of WDPI has been established for urban water planning as a decision making tool. A Graphical User Interface (GUI) of the proposed framework has been developed and applied to Varanasi city where water supply is managed traditionally. The WDPI for Varanasi city is 4.09 (less than 5) which lies in critical condition. Hence, the future planning of the water sector of Varanasi city must reduce the extraction of the water from the natural sources and promote non-conventional practices. © 2019 Elsevier Ltd